3D printing technologies applied to orthoses production - Moya Ferrari, Ana Lya [UNESP] (2019)
The 3D printing has been a constant focus of researches and improvements on existing materials and techniques, offering wide possibilities of application. In the medical field, these techniques are very explored, above all in regard to the production of orthoses. The present study of bibliographic review consists in an analysis of the publications in scientific events and journals available at the Web of Science and Scopus databases, in order to understand how the 3D printing technologies have been used in the production of orthoses. The search strategy used as descriptors: Orthotic Devices; Orthosis; Orthoses; 3D Printing; Additive Manufacture, and returned 332 papers, of which, after analysis, resulted in 27 papers. The results indicate that the main printing techniques used are Fused Deposition Modeling and Selective Laser Sintering. Regarding the materials, the Polylactic Acid and Acrylonitrile Butadiene Styrene are the most used. Most of the researches is concentrated in countries of Europe and North America, with only one study from Brazil, suggesting that this is still a field with wide possibilities to be explored around here.